Wilkawain, surrounding site of the ancient construction and wilkawain geographic context - Maldonado Muñoz, Andrés (2021)
From an architectonic point of view the aim of this article was to study the main Wilkawain construction, in the Peruvian territory; to localize and to place it in Callejón de Huaylas, considering the geographic setting characteristics evaluating the timeline period registered by the archaeology, ancient Peru Middle Horizon as well as the threats and opportunities of the contemporary period for the archaeological monument.